Implementing Biodigester Technology for Sustainable Waste Management in Mojokerto City, Indonesia - Sari, Mega Mutiara; Afifah, Anshah Silmi; Suryawan, I Wayan Koko (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Mojokerto City, located in East Java, grapples with a steadily rising waste generation trend accentuated by the COVID-19 pandemic. Drawing data from the National Waste Management Information System (SIPSN) and supplemented with an exhaustive literature review, this study scrutinizes the potential of biodigester technology as a solution to this mounting challenge. Mojokerto's waste, consistent in its composition from 2019 to 2022, is dominated by food waste, making it an ideal candidate for biodigester intervention. The study revealed that existing biodigester facilities in Mojokerto vary in their waste reduction efficiencies yet collectively demonstrate the viability of converting food waste to energy. For instance, the TPS 3R Magersari Berseri facility showcased an impressive waste reduction rate of 85.0%, processing 62.05 tons out of 73 tons of waste received annually. Comparative analyses of other facilities like TPS 3R Pulorejo "Cahaya Berseri" and TPS 3R Muria Berseri were also conducted, revealing varying degrees of efficiency. These facilities underscore the potential of biodigester technology in managing the rising tide of waste and contributing to sustainable energy generation. The findings of this study also call for increased awareness about food conservation, improved waste segregation at the source, and the promotion of composting and other organic waste processing methods, thereby optimizing the overall efficiency of waste management in the city. .